2012
DOI: 10.3164/jcbn.d-11-00017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of astaxanthin-rich Haematococcus pluvialis extract on cognitive function: a randomised, double-blind, placebo-controlled study

Abstract: In this study we tried to confirm the effect of an astaxanthin-rich Haematococcus pluvialis extract on cognitive function in 96 subjects by a randomised double-blind placebo-controlled study. Healthy middle-aged and elderly subjects who complained of age-related forgetfulness were recruited. Ninety-six subjects were selected from the initial screen, and ingested a capsule containing astaxanthin-rich Haematococcus pluvialis extract, or a placebo capsule for 12 weeks. Somatometry, haematology, urine screens, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 29 publications
1
76
0
Order By: Relevance
“…For example, β-cryptoxanthin has been suggested to reduce the risk of obesity, diabetes, and arteriosclerosis 9 11 . It was also reported that astaxanthin improved the brain function of healthy volunteers who were aware of forgetfulness 12,13 . Furthermore, it is known that lutein and zeaxanthin accumulate in the eyes and are effective for prevention of age-related macular degeneration 14 16 .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, β-cryptoxanthin has been suggested to reduce the risk of obesity, diabetes, and arteriosclerosis 9 11 . It was also reported that astaxanthin improved the brain function of healthy volunteers who were aware of forgetfulness 12,13 . Furthermore, it is known that lutein and zeaxanthin accumulate in the eyes and are effective for prevention of age-related macular degeneration 14 16 .…”
Section: Introductionmentioning
confidence: 92%
“…For example, it is known that supplementation of lutein and/or zeaxanthin can have a protective effect against age-related macular degeneration, which is a major cause of visual impairment in the elderly 30 . In addition, Shirasawa et al reported that oral intake of astaxanthin derived from Haematococcus pluvialis improved cognitive function working memory and response time in healthy volunteers with age-related forgetf u l n e s s 12,13 . T h e r e h a v e a l s o b e e n r e p o r t s t h a t β-cryptoxanthin supplementation may improve conditions such as osteoporosis, hepatic dysfunction, dyslipidemia, and arteriosclerosis 31 37 .…”
Section: Effect Of Paprika Xanthophyll Intake On Reduction Of Abdominmentioning
confidence: 99%
“…Astaxanthin is one of the carotenoids, naturally distributed in crustanceans, such as shrimps and crabs, and fish such as salmons and sea bream (Miki et al, 1982;Matsuno, 2001), and known as a highly potent antioxidant (Miki, 1991;Rodrigues et al, 2012). Recent clinical studies reported that astaxanthin may improve cognitive functions in aged individuals (Katagiri et al, 2012) and that astaxanthin supplementation decreased Ab and phospholipid peroxides in red blood cells in healthy senior subjects (Nakagawa et al, 2011;Kiko et al, 2012). The previous available data suggest that astaxanthin may have a therapeutic or preventive effect on the progression of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was demonstrated that astaxanthin attenuates cognitive disorders in in vivo and in vitro models for neurodegenerative diseases [4,51,52,53]. The first study in measuring carotenoids within brain compartments was carried out by Craft et al [54].…”
Section: Brain Processes Involved In Neurodegeneration and Protectmentioning
confidence: 99%